For love and money: Marital leadership in family firms - Amore, Mario Daniele; Miller, Danny; Le Breton-Miller, Isabelle; Corbetta, Guido (Journal of Corporate Finance, 2017)
We investigate how leadership by couples affects the profitability of family firms. Using comprehensive data from Italy, we show that family firms led by married couples perform significantly better than other family firms. This result is robust to several estimation techniques, including matching, instrumental variables and transition analyses. Marital leadership works best when firm operations are complex and knowledge-based, as well as when the firm is subject to agency conflicts due to weak competition and poor legal infrastructure. Studying the mechanisms behind these results, we show that the presence of couples at the top of the firm enhances the willingness to invest during uncertain times, reduces employee turnover, and improves labor productivity.